Madhya Pradesh Forests and People's Demands a Situation by 2000 A.D. - Tomar, M. S.; Joshi, S. C. (Indian Forester, 1978)
In spite of lack of reliable growing stock and demand information, an attempt has been made to estimate for each district of Madhya Pradesh the existing wood resources, the local demands for fuel wood and timber, projected demands by 2000 A.D. and the additional plantation area needed to meet the growing demand. The total standing volume in M.P. is estimated to be around 589 million m2 and the expected annual cut-put is nearly 12.34 million m2. The total estimated local demands for the entire State are placed at 9.58 million m2 of fuelwood and 1.2 million m2 of timber, showing a surplus Of 1.64 million m2. The projected demand by 2000 A.D. is nearly 20 million m2 with an espected deficit of 8 million m2. Out of 45 distrcts, the 26 districts are already deficit and by end of the present century their number would swell to 39. In order to meet the projected deficit, a total area of 19630 km2 @ 854 km2 per year has to be brought under fuelwood plantation under Social Forestry programme. The annual cost for raising such plantations in the entire state will be around Rs. 128 million. The employment potential for about 60,000 person is expected to be generated. Priority for R & D Programme and importance of remote sensing technique. For survey and mapping of all wastelands, that can be made available for energy plantations, have been indicated. The need for collecting more reliable informationson various aspects has been highlighted.